Grain quality of common bean (Phaseolus vulgaris L.) cultivars under low and high nitrogen dose - Leal, Fabio Tiraboschi [UNESP]; Trombeta Bettiol, Joao Victor [UNESP]; Filla, Vinicius Augusto [UNESP]; Coelho, Anderson Prates [UNESP]; Checchio Mingotte, Fabio Luiz [UNESP]; Lemos, Leandro Borges [UNESP] (Univ Nacional Cuyo, Fac Ciencias Agrarias, 2021)
This study aimed to evaluate the effects of low and high topdressing doses of nitrogen (N) on the qualitative attributes of common beans (Phaseolus vulgaris L.) cultivars and indicate cultivars with better grain technological characteristics. The experimental design was randomized blocks in split plots, with four replicates. Plots comprised 16 common bean cultivars of the commercial grain 'Carioca, while subplots comprised two N doses: 20 and 120 kg ha(-1) applied as topdressing. The following evaluations were carried out: sieve yield (SY), relative grain production on sieves (RGPS), crude protein content (PROT), final water volume absorbed (FVabs), time for maximum hydration (TMH), hydration ratio (HR), cooking time (CT) and resistance to cooking (RC). The results were subjected to analysis of variance by F test and means were grouped by the Scott-Knott test. Multivariate principal component analysis was used to identify processes. Grain quality of common bean resulted to be more dependent on the genotype studied than on the agricultural management, such as nitrogen fertilization. Increasing N dose applied as topdressing increased grain size and protein content, but had little influence on grain hydration. FVabs and CT depended on the interaction between cultivar and N doses. Although low value, CT had an inverse correlation with PROT. The cultivars BRSMG Uai, IAC Alvorada, TAA Dama and TAA Bola Cheia showed the best grain quality characteristics.
Keywords: nitrogen fertilization; genotypes; grain technology; cooking time; protein content